2016
DOI: 10.1177/0269216316676647
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the NECPAL CCOMS-ICO© tool and the Surprise Question as screening tools for early palliative care and to predict mortality in patients with advanced chronic conditions: A cohort study

Abstract: SQ and NECPAL are valuable screening instruments to identify patients with limited life prognosis who may require palliative care. More research is needed to increase its prognostic utility in combination with other parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 53 publications
5
124
0
6
Order By: Relevance
“…We are not aware of any other study validating a 2-step combination of SQ plus general deterioration criteria. A large Spanish study22 reported a similar multistep tool (‘NEPCAL’) including the SQ, general and advanced indicators of disease and did not find significantly better performance of this complex tool compared with the SQ alone, where they identified a PPV of 31% and NPV of 92%, similar to our SQ findings. However, their study was conducted in an advanced chronic disease population in primary and hospital care, rather than a general hospital setting.…”
Section: Discussionsupporting
confidence: 84%
“…We are not aware of any other study validating a 2-step combination of SQ plus general deterioration criteria. A large Spanish study22 reported a similar multistep tool (‘NEPCAL’) including the SQ, general and advanced indicators of disease and did not find significantly better performance of this complex tool compared with the SQ alone, where they identified a PPV of 31% and NPV of 92%, similar to our SQ findings. However, their study was conducted in an advanced chronic disease population in primary and hospital care, rather than a general hospital setting.…”
Section: Discussionsupporting
confidence: 84%
“…As it would be expected, the NECPAL cannot be a tool to limit life measures or access prognosis, as in multivariate regression analysis it was not a predictor of ICU admission or mortality, unlike other scores such as MELD, which are validated for this purpose . Gómez‐Batiste et al found that the NECPAL tool had high sensitivity (91.3, CI: 87.2‐94.2) with high negative predictive value (91.0, CI: 86.9‐94.0) but a very low specificity (32.9, CI: 29.6‐36.3) and low positive predictive value (33.5, CI: 30.2‐36.9), in predicting 12‐month mortality . A potential bias might be related to the fact that identification of at‐risk individuals is based on clinical judgement, which is inherently subjective and can vary depending on the setting or the healthcare professional …”
Section: Discussionmentioning
confidence: 99%
“…It turns out oncologists are fairly adept at sensing when the prognosis has changed, but one useful tip is to routinely ask yourself the “surprise” question: “Would you be surprised if this patient were to die within the next 6 months?”. 16 We have developed this hospice information visit practice to ensure that hospice is brought up as part of a natural transition to end-of-life care. We have not formally tested the tool, but every oncologist we know who has adopted the practice has continued it.…”
Section: The Goc Templatementioning
confidence: 99%